Построение линейной регрессионной модели диффузионного отделения сахарного производства - Ляшенко, С. А. (НТУ "ХПИ", 2014)
В работе сделан анализ процесса диффузии в сахарном производстве и определены основные показатели и параметры работы диффузионного аппарата. Для основных переменных изучаемого технологического процесса получения сока определены статистические характеристики. Получена линейная регрессионная модель диффузионного аппарата. На основании проведенного анализа сделано заключении, что впервые созданная математическая модель, в первом приближении, может быть использована для управления параметрами технологических процессов диффузионного аппарата.

In this paper was made an analysis of the diffusion process in the sugar industry and the basic parameters and the parameters of the diffusion apparatus. The optimal operations of the diffuser (that) allow you to get an effective yield of the raw juice and reduce the amount of feed water and steam heating were selected. For the main variables studied juice extraction process statistical characteristics were defined- mean, variance, median, and the coefficients of skewness and kurtosis. A linear regression model of the diffusion apparatus was found and an analysis on the application of this mathematical model was made. Determining the structure of the model to describe the dependence of the diffusion flow of juice from the other factors of the diffusion process was carried out by stepwise regression identified the coefficient of determination, the consent of the employees measure the regression model with the available data. On the grounds of the analysis was concluded that the mathematical model created for the first time as a first approximation, can be used to control the process parameters of the diffusion apparatus. Determining the significance of the coefficients of the regression model parameters for diffusion apparatus was obtained.
Creation of linear regression model of diffusion separation of sugar production
Keywords: сахарное производство; технологический процесс; диффузия; математическая модель; статистические данные; уравнение регрессии; sugar industry; mathematical model; statistical data; regression equation